Analisis Semantik Dalam Lirik Lagu “O Tuan” Karya Feast - Zico Tri Purnama; Titi Darmi; Delfan Eko Putra (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the semantic meaning contained in the lyrics of the song “O Tuan” by the band Feast using Geoffrey Leech's semantic theory. This study specifically identifies the types of semantic meaning found in the lyrics and analyzes how these meanings contribute to the delivery of spiritual and emotional messages to listeners. The theory used in this study is Geoffrey Leech's semantic theory, which divides meaning into seven types, namely: conceptual meaning, connotative meaning, stylistic meaning, affective meaning, reflected meaning, collocative meaning, and thematic meaning. Leech's theory was chosen because of its comprehensiveness in analyzing various dimensions of meaning in texts, especially expressive texts such as song lyrics. Descriptive qualitative method with content analysis approach. The research data consisted of the lyrics of the song “O Tuan,” which were analyzed using semantic analysis techniques based on Leech's classification of meaning. Data collection techniques were carried out through documentation and observation of the song lyrics, while data analysis techniques used interpretive descriptive analysis with the stages of identification, classification, and interpretation of semantic meaning. The results of the study show that the lyrics of the song “O Tuan” by Feast contain various types of semantic meanings according to Leech's classification. Conceptual meanings are found in the use of words that refer to the concepts of divinity and spirituality. Connotative meanings are seen in the choice of dictionary.